Sea Level Budgets Should Account for Ocean Bottom Deformation - B. D. Vishwakarma; S. Royston; R. E. M. Riva; R. M. Westaway; J. L. Bamber (Geophysical Research Letters)
Abstract The conventional sea level budget (SLB) equates changes in sea surface height with the sum of ocean mass and steric change, where solid‐Earth movements are included as corrections but limited to the impact of glacial isostatic adjustment. However, changes in ocean mass load also deform the ocean bottom elastically. Until the early 2000s, ocean mass change was relatively small, translating into negligible elastic ocean bottom deformation (OBD), hence neglected in the SLB equation. However, recently ocean mass has increased rapidly; hence, OBD is no longer negligible and likely of similar magnitude to the deep steric sea level contribution. Here, we use a mass‐volume framework, which allows the ocean bottom to respond to mass load, to derive a SLB equation that includes OBD. We discuss the theoretical appearance of OBD in the SLB equation and its implications for the global SLB.